BPTF in bone marrow provides a potential progression biomarker regulated by TFAP4 through the PI3K/AKT pathway in neuroblastoma - Chiyi Jiang; Yeran Yang; Sidou He; Zhixia Yue; Tianyu Xing; Ping Chu; Wenfa Yang; Hui Chen; Xiaoxi Zhao; Yongbo Yu; Xuan Zhang; Yan Su; et al. (Biological Procedures Online, 2023)
Abstract Background Neuroblastoma (NB) is the most common extracranial malignant solid tumor in children, which is highly prone to bone marrow (BM) metastasis. BM can monitor early signs of mild disease and metastasis. Existing biomarkers are insufficient for the diagnosis and treatment of NB. Bromodomain PHD finger transcription factor (BPTF) is an important subunit of the chromatin-remodeling complex that is closely associated with tumors. Here, we evaluated whether BPTF in BM plays an important role in predicting NB progression, and explore the molecular mechanism of BPTF in NB. Methods The clinical relevance of the BPTF was predicted in the GEO (GSE62564) and TARGET database. The biological function of BPTF in NB was investigated by constructing cell lines and employing BPTF inhibitor AU1. Western blot was used to determine the changes of BPTF, TFAP4, PI3K/AKT signaling and Epithelial-mesenchymal transition (EMT) related markers. A total of 109 children with newly diagnosed NB in Beijing Children's Hospital from January 2018 to March 2021 were included in this study. RT-PCR was used to measure the BPTF and TFAP4 expression in BM. The cut-off level was set at the median value of BPTF expression levels. Results Databases suggested that BPTF expression was higher in NB and was significantly associated with stage and grade. Proliferation and migration of NB cells were slowed down when BPTF was silenced. Mechanistically, TFAP4 could positively regulate BPTF and promotes EMT process through activating the PI3K/AKT signaling pathway. Moreover, detection of the newly diagnosed BM specimens showed that BPTF expression was significantly higher in high-risk group, stage IV group and BM metastasis group. Children with high BPTF at initial diagnosis were considered to have high risk for disease progression and recurrence. BPTF is an independent risk factor for predicting NB progression. Conclusions A novel and convenient BPTF-targeted humoral detection that can prompt minimal residual and predict NB progression in the early stages of the disease were identified. BPTF inhibitor AU1 is expected to become a new targeted drug for NB therapy. It’s also reveal previously unknown mechanisms of BPTF in NB cell proliferation and metastasis through TFAP4 and PI3K/AKT pathways.